Design for Manufacturability with Advanced Lithography - Yu, Bei.; Pan, David Z.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book introduces readers to the most advanced research results on Design for Manufacturability (DFM) with multiple patterning lithography (MPL) and electron beam lithography (EBL).  The authors describe in detail a set of algorithms/methodologies to resolve issues in modern design for manufacturability problems with advanced lithography.  Unlike books that discuss DFM from the product level, or physical manufacturing level, this book describes DFM solutions from a circuit design level, such that most of the critical problems can be formulated and solved through combinatorial algorithms. Enables readers to tackle the challenge of layout decompositions for different patterning techniques; Presents a coherent framework, including standard cell compliance and detailed placement, to enable Triple Patterning Lithography (TPL) friendly design; Includes coverage of the design for manufacturability with E-Beam lithography.
Introduction -- Layout Decomposition for Triple Patterning -- Layout Decomposition for Other Patterning Techniques -- Standard Cell Compliance and Placement Co-Optimization -- Design for Manufacturability with E-Beam Lithography -- Conclusions and Future Works.-.
Keywords: Electronic circuits; Microprocessors; Computer architecture; Electronics; Electronic Circuits and Systems; Processor Architectures; Electronics and Microelectronics, Instrumentation